The Future of the Renewable Energy in Oman: Case Study of Salalah City - Tabook, Musallam; Khan, Sameen Ahmed (International Journal of Energy Economics and Policy, 2021)
The world-wide energy demand is continuously increasing compounded with global warming. There is an ever-increasing demand in energy accompanied with depletion of fuel stocks, particularly the fossil fuels. The current energy consumption rates are unsustainable and thus have prompted for an active exploration and use of renewable energy sources. In this paper, we shall explore the future of the renewable energy in Oman based on the case study of Salalah city located in Southern Oman. The electricity shortages and the challenges to overcome the increase in electrical demands for the near future are discussed in detail. The climate of any locality is predominantly determined by the amount of sunshine it receives. The duration of sunshine was measured every one hour using the routine sunshine recorders. Our investigations suggest that solar and wind energy will play an important role in the future of renewable energy in Oman. The paper finishes with some conclusions and recommendations. Based on the basic information of Oman solar radiation data, the application of solar energy has a high opportunity to support Oman's power generating capacity. Keywords: Renewable energy, Solar Energy, Wind Energy, Oman. JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.11855